Self-reported knowledge, attitude and mental health status of in-school adolescents in Nigeria - Atinuke O. Olowe; Amme M. Tshabalala; Judith C. Bruce (African Journal of Primary Health Care & Family Medicine)
Background: The global rise in adolescent mental health conditions highlights the need for preventive interventions particularly in schools for timely access to young people, building on inherent strengths and competencies.